Central nervous system tuberculosis in HIV-infected patients: clinical and radiographic findings. - Whiteman, M; Espinoza, L; Post, M J; Bell, M D; Falcone, S (American Journal of Neuroradiology, 1995)
PURPOSE To characterize the radiographic findings on neuroimaging of 25 human immunodeficiency virus (HIV)-seropositive patients with proved central nervous system tuberculosis and to correlate those findings with clinical data. METHODS Twenty-five HIV-seropositive patients with central nervous system tuberculosis were identified, and their imaging studies (CT and, in some cases, MR) and medical records were reviewed. The diagnosis of central nervous system tuberculosis was based on cerebrospinal fluid culture (n = 20), biopsy (n = 4), and/or autopsy (n = 5), with a clinical diagnosis of central nervous system tuberculosis in one additional patient. Results also were correlated with CD4 counts and chest x-ray findings. RESULTS Nine (36%) of 25 patients demonstrated meningeal enhancement. Eleven (44%) of 25 demonstrated enhancing parenchymal lesions; 6 patients had tuberculomata, and 5 had tuberculous abscesses. Communicating hydrocephalus was present in 8 (32%) of 25, and infarction was seen in 9 (36%) of 25. Fifteen of 23 chest x-rays were suggestive of pulmonary tuberculosis. Mean CD4 count was 162. Nine (38%) of 24 patients had a history of pulmonary tuberculosis, and 5 (21%) of 24 had no history of tuberculosis or any other opportunistic infection. Overall mortality was 79%. CONCLUSION Central nervous system tuberculosis has a very high mortality among HIV-infected patients. Because cerebrospinal fluid cultures can take 6 to 8 weeks, the neuroradiologist can play a critical role in patient treatment by suggesting the correct diagnosis based on characteristic imaging findings. Radiographic clues include multiloculated abscess, cisternal enhancement, basal ganglia infarction, and communicating hydrocephalus, which are not findings associated with the more commonly encountered central nervous system lymphoma or toxoplasma encephalitis. Central nervous system tuberculosis may be the initial presentation of acquired immunodeficiency syndrome. In patients with suspected central nervous system tuberculosis, chest x-ray may provide additional support for the diagnosis of tuberculosis.